Structural analysis of composite metakaolin-based geopolymer concrete - F. PELISSER; B. V. SILVA; M. H. MENGER; B. J. FRASSON; T. A. KELLER; A. J. TORII; R. H. LOPEZ (Revista IBRACON de Estruturas e Materiais, 2018)
Abstract The study of alternative binders to Portland cement, such as geopolymer cements, offers the chance to develop materials with different properties. With this purpose, this study evaluated experimentally the mechanical behavior of a geopolymer concrete beam and compared to a Finite Element (FE) nonlinear numerical model. Two concrete beams were fabricated, one of Portland cement and another of metakaolin-based geopolymer cement. The beams were instrumented with linear variable differential transformers and strain gauges to measure the deformation of the concrete and steel. Values for the compressive strength of the geopolymer cement concrete was 8% higher than the Portland cement concrete (55 MPa and 51 MPa, respectively) and the tensile rupture strength was also 8% higher (131 kN) for the geopolymer concrete beam in relation to Portland cement concrete beam (121 kN). Distinct failure mechanisms were verified between the two samples, with an extended plastic deformation of the geopolymer concrete, revealing post-fracture toughness. The geopolymer concrete showed higher tensile strength and better adhesion in cement-steel interface.